The method of teaching vocabulary in a foreign language - Madaminova Umida Rustam qizi (Genius Journals, 2022)
The article illustrates the important features of vocabulary in receiving knowledge in foreign language. The author of the article analyses the core hypothesis of vocabulary, crucial strategies, vital techniques, variety instruction and various approaches (methods) theoretically and practically
Keywords: Vocabulary; strategy; planning; knowledge